Peningkatan Pengetahuan dan Keterampilan Sumberdaya Manusia Berbasis BPOM Pada Teaching Factory Pengolahan Kopi - Rosdiana, Eva; Kusumaningtyas, Rizky Nirmala; Pratita, Dian Galuh; Hartatie, Dian (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
The Jember State Polytechnic Coffee Product Processing Teaching Factory focuses on ground coffee made from Robusta and Argopuro Arabica coffee. Increasing its existence as a small industry requires binding legalization of products and consistency from human resources who carry out an industry-based work culture, in this case, contained in the legalization of BPOM. Therefore, this service focuses on introducing an industry-based work environment (BPOM). The methods used in this service include counseling and direct practice at Tefa locations where coffee products are processed. Based on the service results, the human resources involved in Tefa's coffee product processing operations are enthusiastic in the counseling process and have a high interest in changing behavior in implementing an industry-based work environment.